Do Investors Perceive Low Risk When Earnings are Smooth Relative to the Volatility of Operating Cash Flows? Discerning Opportunity and Incentive to Report Smooth Earnings - Erickson, Devon; Hewitt, Max; Maines, Laureen A. (The Accounting Review, 2017)
ABSTRACT A fundamental accounting question is whether investors perceive low risk when earnings are smooth relative to the volatility of operating cash flows. We conduct two experiments to examine this question. Absent additional information concerning the likelihood of earnings management, our first experiment finds that investors give managers the benefit of the doubt and perceive low risk when earnings are relatively smooth. Given this finding, our second experiment examines whether additional information that supports investors' suspicions of earnings management affects investors' risk judgments when earnings are relatively smooth. We find that investors no longer give managers the benefit of the doubt when additional information suggests that managers have either the opportunity or the incentive to report smooth earnings. Our study provides important insights to the literature concerning both “whether” and “when” relatively smooth earnings affect investors' risk judgments. Data Availability: Contact the authors.